Day-case holmium laser enucleation of the prostate. (July 2015) - Cynk, Mark; Georgiadis, Georgios; Moore, Emily; Appleby, Jonathan; Griffiths, Richard; Hale, Jemma
In 2011 day-case prostate surgery was selected for financial incentives in the UK by the Department of Health Payment by Results (PbR) scheme, with a target of 30% of holmium laser enucleation of the prostate (HoLEP) procedures as day cases for 2011–2012, increasing to 90% within three years. The objective was to determine the feasibility and safety of day-case HoLEP. Patients and methods: All patients presenting to an experienced HoLEP surgeon and requiring prostatic surgery were considered for day-case HoLEP. We developed a four-hour postoperative discharge protocol with specialist urology nurse assessment and discharge. Results: Between April 2011 and March 2014, 188 patients (median age 74, range 48–92) were eligible for HoLEP surgery. Four patients did not undergo surgery, and 70 (38%) did not fit the day-case criteria. The remaining 114 (62%) were considered for day surgery, of which 91 (80%) were successful. There was one readmission with haematuria and blocked catheter, and two late readmissions with secondary bleeding. Conclusions: Day-case HoLEP is feasible and safe, even in patients with significant comorbidity. Our overall day-case rate of 49.5% exceeds the initial 30% target set by PbR, but suggests that the 90% target is overly optimistic.